Frequency Selective Surfaces based High Performance Microstrip Antenna - Narayan, Shiv.; Sangeetha, B.; Jha, Rakesh Mohan; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book focuses on performance enhancement of printed antennas using frequency selective surfaces (FSS) technology. The growing demand of stealth technology in strategic areas requires high-performance low-RCS (radar cross section) antennas. Such requirements may be accomplished by incorporating FSS into the antenna structure either in its ground plane or as the superstrate, due to the filter characteristics of FSS structure. In view of this, a novel approach based on FSS technology is presented in this book to enhance the performance of printed antennas including out-of-band structural RCS reduction. In this endeavor, the EM design of microstrip patch antennas (MPA) loaded with FSS-based (i) high impedance surface (HIS) ground plane, and (ii) the superstrates are discussed in detail. The EM analysis of proposed FSS-based antenna structures have been carried out using transmission line analogy, in combination with the reciprocity theorem. Further, various types of novel FSS structures are considered in designing the HIS ground plane and superstrate for enhancing the MPA bandwidth and directivity. The EM design and performance analyses of FSS-based antennas are explained here with the appropriate expressions and illustrations.
Introduction -- Characteristics of FSS Structures -- Microstrip Antenna over FSS based High Impedance Ground Plane -- Microstrip Antenna Loaded with FSS based Superstarte -- Summary.
Keywords: Engineering; Physics; Microwaves; Optical engineering; Electrical engineering; Engineering; Microwaves, RF and Optical Engineering; Theoretical, Mathematical and Computational Physics; Communications Engineering, Networks; Electronic books